Intercalated vs Nonintercalated Morphologies in Donor-Acceptor Bulk Heterojunction Solar Cells: PBTTT:Fullerene Charge Generation and Recombination Revisited. - Collado-Fregoso,E; Hood,SN; Shoaee,S; Schroeder,BC; McCulloch,I; Kassal,I; Neher,D; Durrant,JR (Journal of Physical Chemistry Letters, 2017)
In this Letter, we study the role of the donor:acceptor interface nanostructure upon charge separation and recombination in organic photovoltaic devices and blend films, using mixtures of PBTTT and two different fullerene derivatives (PC70BM and ICTA) as models for intercalated and nonintercalated morphologies, respectively. Thermodynamic simulations show that while the completely intercalated system exhibits a large free-energy barrier for charge separation, this barrier is significantly lower in the nonintercalated system and almost vanishes when energetic disorder is included in the model. Despite these differences, both femtosecond-resolved transient absorption spectroscopy (TAS) and time-delayed collection field (TDCF) exhibit extensive first-order losses in both systems, suggesting that geminate pairs are the primary product of photoexcitation. In contrast, the system that comprises a combination of fully intercalated polymer:fullerene areas and fullerene-aggregated domains (1:4 PBTTT:PC70BM) is the only one that shows slow, second-order recombination of free charges, resulting in devices with an overall higher short-circuit current and fill factor. This study therefore provides a novel consideration of the role of the interfacial nanostructure and the nature of bound charges and their impact upon charge generation and recombination.